Speech vs. touch-tone: Telephony interfaces for information access by low literate users - Sherwani, J.; Palijo, S.; Mirza, S.; Ahmed, T.; Ali, N.; Rosenfeld, R. (2009 International Conference on Information and Communication Technologies and Development, 2009)
Information access by low literate users is a difficult task. Critical information, such as in the field of healthcare, can often mean the difference between life and death. We have developed spoken language interface prototypes aimed at low literate users, and tested them with community health workers in Pakistan. We present results showing that 1) in contrast to previous reports in the literature, well-designed speech interfaces significantly outperform touch-tone equivalents for both low-literate and literate users, and that 2) literacy significantly impacts task success for both modalities.